2019
DOI: 10.3389/fimmu.2019.01318
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Immunogenicity of African Swine Fever Virus Antigens

Abstract: African swine fever (ASF) is a lethal haemorrhagic disease of domestic pigs for which there is no vaccine. Strains of the virus with reduced virulence can provide protection against related virulent strains of ASFV, but protection is not 100% and there are concerns about the safety profile of such viruses. However, they provide a useful tool for understanding the immune response to ASFV and previous studies using the low virulent isolate OUR T88/3 have shown that CD8+ cells are crucial for protection. In order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
142
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(151 citation statements)
references
References 73 publications
8
142
0
1
Order By: Relevance
“…This may be related to the diverse functions of MGF proteins reported in previous studies (L. Dixon, Islam, Nash, & Reis, 2019; Netherton et al, 2019). For example, it is reported that the MGF proteins were associated with the virulence, antigenicity and immune escape of ASFVs (Burrage, Lu, Neilan, Rock, & Zsak, 2004; Golding et al, 2016).…”
Section: Discussionsupporting
confidence: 57%
“…This may be related to the diverse functions of MGF proteins reported in previous studies (L. Dixon, Islam, Nash, & Reis, 2019; Netherton et al, 2019). For example, it is reported that the MGF proteins were associated with the virulence, antigenicity and immune escape of ASFVs (Burrage, Lu, Neilan, Rock, & Zsak, 2004; Golding et al, 2016).…”
Section: Discussionsupporting
confidence: 57%
“…We ascertain the genetic properties of the genes with positive diversifying selection or selective sweep by calculating population prevalence frequencies and pair-wise amino acid divergence of the genes and doing comparison with three gene categories cataloged from other studies: (i) the non-antigenic conserved structural proteins without positive selection (32), (ii) the antigen proteins eliciting immunological responses in immunoassay experiments (40)(41)(42), (iii) the proteins previously shown to be involved in host cell interactions (10,43) ( Figure 4 and Table S6). A non-uniform population prevalence and higher level of sequence variability are observed in the candidate genes under putative positive diversifying selection in comparison with the category of (i) conserved structural proteins and (ii) antigenic proteins, but not with the gene category (iii) involved in host cell interactions (two-sided Mann-Whitney U-test, Figure 4a…”
Section: Sequence Variability Of the Candidate Genes With Diversifyinmentioning
confidence: 99%
“…The CD8α chain forms part of the heterodimer coreceptor for TcR engagement with MHC class I-peptide complexes. Initially thought to be a mechanism to aid peripheral tolerance, CD8 down-regulation on primed/activated T cell populations has been described in both humans and mice in a variety of contexts including in response to infection [81][82][83][84]. We therefore speculate that a combination of the magnitude of the BoHV-4 vector induced T cell response and the high concentrations of peptides used in the recall assay may have contributed to the decreased CD3/CD8α surface expression.…”
Section: Discussionmentioning
confidence: 95%